The Adventures of Ibn Battuta - Dunn, Ross E.
1 online resource (307 pages)
Keywords: Ross Dunn here recounts the great traveler's remarkable career, interpreting it within the cultural and social context of Islamic society and giving the reader both a biography of an extraordinary personality and a study of the hemispheric dimensions of human interchange in medieval times.